Síntese e caracterização da metilcelulose, a partir do bagaço de cana-de-açúcar, para utilização como aditivo na construção civil - Vieira, Júlia Graciele (2009)
In the present work, methylcellulose was produced from sugarcane bagasse cellulose. The synthesis was carried out by heterogeneous route, in alkaline medium, using dimethyl sulfate (DMS) as methylating agent, with 5 hours of reaction and reagent substitution at each hour. Produced methylcellulose was characterized by Fourier Transformed Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and Chemical determination of the methoxyl groups and Degree of Substitution (DS). The value obtained for the degree of substitution was 1.89 ± 0.04. An aqueous viscous suspension of methylcellulose, 0.6% w/w ( weight of polymer/ weight of cement), was applied as admixture for mortars and its effect was evaluated in fresh state by essays of Consistency Index (CI), and in the hardened state by Potential Tensile Adhesion Strength. It was observed a 40.37% (± 0.70) increase on the Consistency Index (CI) and a 27.70% (± 0.06) increase on the potential tensile adhesion strength. The methylcellulose showed satisfactory results to be applied as viscosity enhancing admixture in mortars for settling tile, recoverings and finishings.